2018
DOI: 10.1155/2018/7285483
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Exciton Generation in Nanostructures for Advanced Photovoltaic Cells

Abstract: is paper reviews both experimental and theoretical work on nanostructures showing high quantum yields due to the phenomenon of multiple exciton generation. It outlines the aims and barriers to progress in identifying further such nanostructures and also includes important developments concerning solar devices where nanostructures act as the light-absorbing component. It reports on both semiconductor and carbon structures, both monocomposite (of various dimensionalities) and heterogeneous. Finally, it looks at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 94 publications
(182 reference statements)
0
8
0
Order By: Relevance
“…GCESb 2 S 3 was observed at a lower characteristic frequency compared to GCEBi 2 S 3 and indicated that GCESb 2 S 3 was experienced at a slower charge recombination rate. , The redox diffusion of about 126 Hz was the slowest process among the charge transfer in all of the modified electrodes; hence, the determining process was associated with the electrocatalytic activity. , Although Sb 2 S 3 was observed at a lower frequency, it was found to be considerably more than the frequency of the redox diffusion process in an electrolyte interface of solar cells. Hence, it completely meets the requirements for charge transfer in a photovoltaic cell. , …”
Section: Resultsmentioning
confidence: 88%
“…GCESb 2 S 3 was observed at a lower characteristic frequency compared to GCEBi 2 S 3 and indicated that GCESb 2 S 3 was experienced at a slower charge recombination rate. , The redox diffusion of about 126 Hz was the slowest process among the charge transfer in all of the modified electrodes; hence, the determining process was associated with the electrocatalytic activity. , Although Sb 2 S 3 was observed at a lower frequency, it was found to be considerably more than the frequency of the redox diffusion process in an electrolyte interface of solar cells. Hence, it completely meets the requirements for charge transfer in a photovoltaic cell. , …”
Section: Resultsmentioning
confidence: 88%
“…In this review our focus will be on the latter, and for work on MEG in various nanostructures we refer to existing reviews. 41,42 A key challenge in the realization of a HCPV device is the inherent nature of hot carriers to relax very rapidly (order of ps) 3 . Efforts therefore typically focus on one of two aspects: slowing down the relaxation process of hot carriers; and designing contacts that can extract hot carriers at elevated temperatures/energies, before they lose their heat to the lattice.…”
Section: Hot-carrier Photovoltaicsmentioning
confidence: 99%
“…101,[105][106][107][108] In the last few years several review articles dedicated to CM in NCs have appeared discussing the advancements in this fascinating field. 1,2,18,[25][26][27]84,[109][110][111][112][113][114][115][116][117][118][119][120][121][122][123][124][125] However, these reviews were mainly dedicated to the case of chalcogenide and in particular lead-chalcogenide NCs. 27,120,125,126 Lead-chalcogenides (mainly PbS and PbSe) possess small electron and hole masses as well as a large Bohr exciton radius, which favors a strong quantum confinement effect.…”
Section: Introductionmentioning
confidence: 99%